Your money or your data. (Economist, 2015)
The article looks at computer hacking and computer crime, focusing on criminals growing use of ransomeware, or computer viruses that encrypt the files of the infected computer, forcing the owner to pay a ransom for the decryption key in order to regain his or her data. Topics include typical ransom payments and cybercriminals use of the virtual currency bitcoin.